EFFECT OF DEXTERITY AND GENDER ON FINGERNAIL CONFIGURATION IN MEDICAL STUDENTS (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Identification is a very important aspect of criminal investigation. Corpus delicti clearly explains the importance of positive identification in the criminal justice system. Various studies in the past have proved that nails vary very little with season. The anthropology of the nail can therefore become a very important tool for identification. Materials and methods: A cross sectional study was conducted on the 4th and 6th semester medical trainees which included 125 male and 125 female medical trainees. The width of the fingernail and the radius of Transverse Curvature was measured. Result: The median of W/L ratio of dominant hands was found to be greater than that of non-dominant hands. The study proves that the extent of mechanical stress onthe respective hand can possibly influence the size and shape of the nail plate. The study also showed that the median value of both the W/L and Radius of Curvature was more in males compared to females.
Keywords: Identification; Fingernail; Anthropology; Dexterity; Gender